The relevance of particle interactions in nanoparticulate systems - Application to particulate thin films - Günther, Lydia; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2002)
In the field of Particle Technology, processes cannot yet be designed from basic molecular understanding. Nanotechnology, however, begins to bridge this gap between molecules and particles and may thus open up new ways not only for the production and handling of particulate matter but also for the engineered design of advanced material properties. The visions and applications in nanoparticle technology cover a broad range, for instance quantum dots in information technology, refractory particles for advanced ceramics, highly active substances in pharmacy, catalysts or micro- and mesoporous adsorbents, to name only a few applications. Starting from the concept of product engineering, we investigate the basic preconditions for tailoring nanoparticulate properties, i.e. the control of the particle interactions. This concept is then applied to particulate thin film formation as an example of structure formation. The structure of dip-coated samples, defined as the order of particles within the layer, was found to vary with the pH and the ion concentration adjusted in the sol bath. It was observed that the surface roughness scanned by an atomic force microscope increased with increasing electrolyte concentration. The structural evolution of the particulate network was studied by measuring the viscosity as a function of shear rate and solid concentration. Finally, the influence of coating structures on the transmission properties was determined. Especially in the case of LaCl3 a strong dependence was observed. The results explicitly confirm a correlation between microscopic structure and macroscopic properties.
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.therel